Analisis Peraturan Menteri Nomor PER.02/MEN/III/2008 Tentang Tata Cara Penggunaan Tenaga Kerja Asing di Indonesia - Herma Diana (Jurnal Ekonomia, 2019)
Realizing the reality so far Indonesia still needs foreign investors, as well as the influence of globalization of civilization where Indonesia as a WTO member country must open up opportunities for foreign workers to enter. To anticipate this, it is expected that there will be a complete set of regulations governing the requirements of foreign workers, as well as securing the use of foreign workers. The regulation must regulate the basic aspects and forms of regulation that regulate not only at the Ministerial level, with the aim of using foreign workers selectively while still prioritizing migrant workers. Therefore, in employing foreign workers, it is carried out through very strict mechanisms and procedures, especially by requiring companies or corporations that use foreign workers to work in Indonesia by making plans to use foreign workers (RPTKA) as stipulated in Ministerial Regulation Number PER .02 / MEN / III / 2008 concerning Procedures for the Use of Foreign Workers. The development of globalization has led to a movement of capital flows and investment to various parts of the world, and there has also been population migration or movement of labor between countries. The movement of labor takes place because investments made in other countries generally require direct supervision by the owner / investor. In line with that, in order to maintain the continuity of the business and its investment. To avoid the occurrence of legal problems and excessive use of foreign labor, the Government must carefully determine the policies that will be taken to maintain a balance between foreign workers (foreign capital) and domestic workers.